A Macrocyclic Fluorophore Dimer with Flexible Linkers: Bright Excimer Emission with a Long Fluorescence Lifetime. Issue 25 (28th April 2016) - Osaki, Hiroshi; Chou, Chih‐Ming; Taki, Masayasu; Welke, Kai; Yokogawa, Daisuke; Irle, Stephan; Sato, Yoshikatsu; Higashiyama, Tetsuya; Saito, Shohei; Fukazawa, Aiko; Yamaguchi, Shigehiro
Abstract: Bright fluorescent molecules with long fluorescence lifetimes are important for the development of lifetime‐based fluorescence imaging techniques. Herein, a molecular design is described for simultaneously attaining long fluorescence lifetime ( τ ) and high brightness ( Φ F × ɛ ) in a system that features macrocyclic dimerization of fluorescent π‐conjugated skeletons with flexible linkers. An alkylene‐linked macrocyclic dimer of bis(thienylethynyl)anthracene was found to show excimer emission with a long fluorescence lifetime ( τ ≈19 ns) in solution, while maintaining high brightness. A comparison with various relevant derivatives revealed that the macrocyclic structure and the length of the alkylene chains play crucial roles in attaining these properties. In vitro time‐gated imaging experiments were conducted as a proof‐of‐principle for the superiority of this macrocyclic fluorophore relative to the commercial fluorescent dye Alexa Fluor 488. Abstract : Brighter and slower : A macrocyclic fluorophore dimer with flexible alkylene linkers exhibited strong absorption, a high fluorescence quantum yield ( Φ F ), and a slow fluorescence decay ( τ ) attributable to efficient intramolecular excimer formation. In vitro time‐gated imaging experiments were used to demonstrate the superior fluorescence performance of the dimer compared to a commercial fluorescent dye.